The belle of Chatham - Frantz, Laura (Revell, a division of Baker Publishing Group, 2026)
"In 1777, suspicions of betrayal engulf Maebel Bohannon's family when the American Revolution turns her New Jersey village into a battlefield and renders her sister a British spy. Maebel's growing affection for an American general and her family's disapproval widen the chasm between love and loyalty. When her survival is threatened, she must decide whether liberty is worth its price"-- Provided by publisher.